2020
DOI: 10.1007/s12098-020-03235-w
|View full text |Cite
|
Sign up to set email alerts
|

Airway Pressure Release Ventilation as a Rescue Therapy in Pediatric Acute Respiratory Distress Syndrome

Abstract: Objectives To describe experience with airway pressure release ventilation (APRV) in children with severe acute respiratory distress syndrome (ARDS) refractory to conventional low tidal volume ventilation. Methods This retrospective observational study was performed in an 11-bed, level 3 pediatric intensive care unit. Evaluation was made of 30 pediatric patients receiving airway pressure release ventilation as rescue therapy for severe ARDS. Results Patients were switched to APRV on an average 3.2 ± 2.6 d foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…A similar study found that survival in immunocompromised patients with ARDS was significantly associated with improved oxygenation 24 h after transition to APRV or HFOV (102). A recent retrospective analysis of 30 pediatric patients with severe PARDS transitioned from CMV to APRV for refractory hypoxemia found that the SpO 2 / FiO 2 ratio increased from 132 to 165, likely secondary to increased mPaw with a lower PIP, and a mortality rate of 17% (103). Previous small pediatric case series/case reports also observed improved oxygenation at lower peak airway pressure (93,94,97,99) and no adverse hemodynamic effects (95,96).…”
Section: Retrospective Case Seriesmentioning
confidence: 84%
See 1 more Smart Citation
“…A similar study found that survival in immunocompromised patients with ARDS was significantly associated with improved oxygenation 24 h after transition to APRV or HFOV (102). A recent retrospective analysis of 30 pediatric patients with severe PARDS transitioned from CMV to APRV for refractory hypoxemia found that the SpO 2 / FiO 2 ratio increased from 132 to 165, likely secondary to increased mPaw with a lower PIP, and a mortality rate of 17% (103). Previous small pediatric case series/case reports also observed improved oxygenation at lower peak airway pressure (93,94,97,99) and no adverse hemodynamic effects (95,96).…”
Section: Retrospective Case Seriesmentioning
confidence: 84%
“…Disadvantages of APRV include difficulty of controlling VT, concern for atelectrauma during releases (especially in lung units with low compliance and resistance), and exposure to high transpulmonary pressure during spontaneous breathing at P-high. Current data evaluating APRV in children are limited to single center case series as a rescue mode for patients with refractory hypoxemia and one small, single center RCT (93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103).…”
Section: Aprvmentioning
confidence: 99%
“… [82] 2010 America Crossover APRV vs. CV 12 P plat or PIP Higher than T low PEEP Higher than T low Increased Increased P mean Similar / / Yehya et al . [51] 2013 America Crossover APRV vs. HFOV 104 P mean / 0 cm H 2 O 50–75% PEF / / / / Similar ofsurvival Yener and Udurgucu [83] 2020 Turkey Crossover APRV vs. CV 30 / / 0 cm H 2 O Prevents end-expiratory pressure from reaching zero Increased Reduced PIP, increased P mean / / / Kawaguchi et al . [84] 2015 Japan Case series APRV 13 P plat 3.0–5.0 s 0 cm H 2 O 0.2–0.6 s Similar Increased P mean Similar / / ALI: Acute lung injury; APRV: Airway Pressure Release Ventilation; ARDS: Acute respiratory distress syndrome; CV: Conventional ventilation; HFOV: High frequency oscillatory ventilation; LTV: Low tidal volume; PEEP: Positive end expiratory pressure; PEF: Peak expiratory flow; PEFR: Peak expiratory flow rate; P high : High pressure; PIP: Inspiratory peak pressure; P low : Low pressure; P mean : Mean airway pressure; P plat : Platpressure; RCT: Randomized controlled study; SIMV: Synchronized intermittent mandatory ventilation; T high : High pressure time; T ...…”
Section: Application Of Aprv In Ardsmentioning
confidence: 99%
“…Airway pressure release ventilation (APRV) is a mode of mechanical ventilation consisting of the application of continuous positive airway pressure with time-cycled pressure releases [ 1 ]. APRV is widely available on existing ventilators, and has been proposed as an early intervention to prevent lung injury [ 2 ] or as a rescue therapy in the management of refractory hypoxemia [ 3 ]. Some benefits of the approach are associated with the fact that it readily permits the preservation of spontaneous breathing by the patient.…”
Section: Introductionmentioning
confidence: 99%